Hypothetic Model of Learning Facilitation Based on Students' Problems and Expectations in Quick Completion of Study on Time - Asep Saepudin; Iip Saripah; Viena Rusmiati Hasanah; Ani Rindiani; Faridah Hanim Yahya (Journal of Nonformal Education, 2024)
Completion of studies on time is the hope of every student, in addition to achieving very satisfying academic achievements. Despite these hopes, currently many doctoral program students at the Faculty of Education, Indonesian Education University are not graduating on time. For this reason, research needs to be carried out to find out the reasons and efforts to resolve it. The aim of the research is to find students' problems and hopes in completing their studies quickly. This research method uses Research and Development with data collection techniques in the form of questionnaires, interviews and documentation. The research results show that firstly, empirically the completion of student studies is still relatively low, as evidenced by the number of students who have not graduated at 72%. Second, student affairs problems consist of relatively diverse academic and non-academic problems, including student expectations of lecturers and study program services. Third, based on students' problems and expectations, a learning facilitation service model is needed. The research conclusion is that it is necessary to develop a learning facilitation model design consisting of background, objectives, assumptions, principles, system components, procedures and indicators of success. This research produces a model design as a novelty that contributes to higher education leaders, academic supervisors, and administrative staff to provide services to students in completing studies quickly on time.